Formulation and Characterization Tests of SCOBY Kombucha Gel - Agustina, Eva; Nafisah, Raihana Frika; Fiddaroini, Achmad Farchan; Tania, Clarista Eka; Purnamasari, Risa; Andiarna, Funsu; Hidayati, Irul (Biology, Medicine, & Natural Product Chemistry, 2025)
The wound is the damage to body tissues caused by various factors such as accidents, sharp object scratches, etc. Proper care is necessary to accelerate the wound healing process. Topical medications, such as gel preparations, are commonly used for wounds. Kombucha SCOBY is believed to contain bioactive compounds that can accelerate the wound healing process, making it a potential active ingredient in gel preparations. This research aims to determine the characteristics of kombucha SCOBY gel with various concentration variations. SCOBY is obtained from kombucha fermentation using green tea, sugar, and kombucha culture. Preparing kombucha SCOBY gel involves using carbomer 940, methyl paraben, triethanolamine, glycerin, and SCOBY kombucha. The concentration variations of kombucha SCOBY gel include 0%, 2%, 4%, 8%, 10%, and 12%. Each formula undergoes physical characteristic tests including an organoleptic test, hedonic test, homogeneity test, pH test, spreadability test, and adhesiveness test. Data obtained after physical characteristic tests of the gel preparations are analyzed descriptively. Based on the conducted research, it was found that kombucha SCOBY gel preparations with concentration variations of 0%, 2%, 4%, 8%, 10%, and 12% exhibited different characteristics. The higher the gel concentration, the more acidic the gel's aroma, the more liquid the texture, and the more intense the color. SCOBY added to the gel preparation can increase the pH value, adhesiveness, and spreadability of the gel.